Hinduism - Andrews, Elizabeth, 1996- (Minneapolis, Minnesota : DiscoverRoo, an imprint of Pop!, 2024)
This books explores the history and contains an explanation of the beliefs and practices of Hinduism.
Brahman and sacred texts -- Dharma and Samsara -- Reaching Moksha -- Colorful celebrations.
Includes index.
6.4
3-6
800L
Keywords: Hinduism -- Juvenile literature; Hinduism; Religions -- Juvenile literature